Vegetation Classification and Survey: five years and looking ahead - Idoia Biurrun; Jürgen Dengler; Wolfgang Willner (Vegetation Classification and Survey (VCS))
This editorial opens the sixth volume of Vegetation Classification and Survey (VCS), a gold open access journal of the International Association for Vegetation Science (IAVS). On occasion of the fifth anniversary of the start of the journal, we provide an analysis of the 119 articles published from 2020 to 2024, focusing on their content, geographic scope, article category and the collection they belong to, if any. For articles that performed a plot-based classification, we provide information on classification approach, plot size, importance value, taxonomic coverage, number of plots, and classification algorithm. We also analyze the bibliometric performance of VCS across the five years and predict a CiteScore of 3.6 and a Journal Impact Factor of 2.7 for 2024 (to be published in 2025). Using the Field-Weighted Citation Impact (FWCI) from the Scopus database, we identified the nine VCS articles published in the first five years that received at least twice as many citations as expected for their age and field. Next we present the four Editors’ Choice papers of 2024, among which Naftal et al. (2024; Vegetation Classification and Survey 5: 127–151) received the Editors’ Award. We conclude that VCS is on the right track, although we would like to encourage the submission of more classification papers based on large plot datasets, as well as methodological papers and comprehensive reviews. Abbreviations: CCCN = Committee for Changes and Conservation of Names; FWCI = Field-Weighted Citation Impact; JIF = Journal Impact Factor; IAVS = International Association for Vegetation Science; VCS = Vegetation Classification and Survey.